2011
DOI: 10.1089/dna.2010.1129
|View full text |Cite
|
Sign up to set email alerts
|

TheCD40Gene Polymorphism rs1883832 Is Associated with Risk of Acute Coronary Syndrome in a Chinese Case–Control Study

Abstract: Numerous reports in the past few years have demonstrated that atherosclerosis is a lipid-driven, chronic inflammatory disease of the vessel. Recent studies have indicated that the immune mediator CD40-CD40L (CD40 ligand), which is expressed on several inflammatory cells within human atherosclerotic lesions, has roles in atherogenesis. A functional polymorphism (-1C>T, rs1883832) in the 5' untranslated region of TNFRSF5 gene has been reported to affect CD40 expression and be associated with several chronic infl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 33 publications
2
23
0
1
Order By: Relevance
“…In this study, we showed that the CD40 -1 C/T polymorphism can cause the alteration of CD40 translation on human B cells. The expression of CD40 in the individuals with TT genotype was significantly lower than those with CC and CT genotypes in both ASC and control groups, which is agreement with other studies [25,33]. Our findings that the frequency of TT genotype was significantly higher in ASC groups might be understood as follows: TT genotype of CD40-1C/T polymorphism decreases CD40 expression on cell surface as we and others confirmed.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…In this study, we showed that the CD40 -1 C/T polymorphism can cause the alteration of CD40 translation on human B cells. The expression of CD40 in the individuals with TT genotype was significantly lower than those with CC and CT genotypes in both ASC and control groups, which is agreement with other studies [25,33]. Our findings that the frequency of TT genotype was significantly higher in ASC groups might be understood as follows: TT genotype of CD40-1C/T polymorphism decreases CD40 expression on cell surface as we and others confirmed.…”
Section: Discussionsupporting
confidence: 92%
“…Co., Ltd. Hangzhou, China). CD40-1C/T polymorphism was determined by polymerase chain reaction (PCR) and the analysis of restriction fragment lengths polymorphism (RFLP) as previously reported [25]. PCR was performed to amplified the 5'-untranslated region of CD40 using the following primers: 5'-GAAACTCCTGCGCGGTGAAT-3' and 5'-CCTCTTCCC- CGAAGTCTTCC-3' (NCBI Reference Sequence: NC_000020.11).…”
Section: Subject and Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Ultimately, 7 studies (5 on coronary artery disease [CAD] and 2 on ischemic stroke [IS]) involving a total of 4024 subjects (2129 patients and 1895 controls) met our criteria and were included in this meta-analytical study [6], [7], [13]–[17]. The corresponding authors of our included studies were contacted and they confirmed that there were no duplicate results utilized in multiple studies to be deleted.…”
Section: Resultsmentioning
confidence: 99%
“…In Grave’s disease, up-regulation of CD40 by rs1883832 places an individual at an increased disease risk [28]. Similarly, C allele appeared to contribute to the over-expression of CD40 on not only platelets which are central to the formation of thrombosis in ACS patients, but also B lymphocytes and monocytes [7], [15], [17]. C allele is also positively associated with an increased risk of rupture of complex coronary atherosclerotic plagues underlying ACS [17].…”
Section: Discussionmentioning
confidence: 98%